2014
DOI: 10.1007/s10620-014-3327-8
|View full text |Cite
|
Sign up to set email alerts
|

A Rapid and Accurate Method to Detect Active Small Bowel Gastrointestinal Bleeding on Video Capsule Endoscopy

Abstract: The QV + SBI reading format of VCE is an efficient, highly sensitive modality to assess for potential small bowel bleeding.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…Previously, Stein et al utilized the Quickview function in the RAPID Reader software v6.0 in conjunction with the SBI function and found an overall sensitivity of 100% in detecting 28 cases of active small bowel bleeding [ 7 ]. Tal et al utilized the SBI function alone and also found 100% sensitivity in detecting 42 cases of active small bowel bleeding, with a mean of 46.6 SBI bars in major bleeding cases and a mean of 36 SBI bars in minor bleeding cases [ 8 ].…”
Section: Discussionmentioning
confidence: 99%
“…Previously, Stein et al utilized the Quickview function in the RAPID Reader software v6.0 in conjunction with the SBI function and found an overall sensitivity of 100% in detecting 28 cases of active small bowel bleeding [ 7 ]. Tal et al utilized the SBI function alone and also found 100% sensitivity in detecting 42 cases of active small bowel bleeding, with a mean of 46.6 SBI bars in major bleeding cases and a mean of 36 SBI bars in minor bleeding cases [ 8 ].…”
Section: Discussionmentioning
confidence: 99%
“…In order to reduce the possibility of missing lesions and the reading time required, several software modes have been developed including the Blood indicator 10 11 12 , Blue mode 13 14 , Flexible spectral Imaging Color Enhancement (FICE) 15 , Automatic mode 7 , and Quickview 8 16 . The Blood indicator selects red (blood) images 10 11 12 while Blue mode enhances lesions that are blue 14 15 . FICE is based on the arithmetic narrowing of the bandwidth of a conventional endoscopic image using computerized spectral estimation technology to enhance the lesion, thus simplifying detection 17 .…”
Section: Discussionmentioning
confidence: 99%
“…To overcome SBCE limitations and reduce reporting time while reviewing SBCEs, several artificial intelligence-based viewing modes are currently available on SBCE reading platforms [54][55][56]. Quickview automatically skips similar images and the suspected blood indicator (SBI) is a pixel analysis programme that identifies suspected blood.…”
Section: Challenges Associated With Artificial Intelligencementioning
confidence: 99%